Perancangan Sistem Informasi Pemesanan Tiket Kereta Api Layanan Lokal Palembang Raya Berbasis Aplikasi KAI Access (Studi Kasus Pada PT KAI) - Nabila Miftha Huljanah; Fenny Purwani; Kristin Kristin; Apriani Apriani; Nindy Tri Buana (CV. Denasya Smart Publisher, 2025)
In this era of technology, to handle several obstacles in conventional ticket ordering such as long queues at the station, limited time owned by consumers, the process of delivering information about ticket prices for the day of departure or previous dates that cannot be processed, PT Kereta Api Indonesia (KAI) provides a solution through the KAI Access application which will facilitate ticket ordering, fast transaction process, reduce operational costs when ordering tickets, delivery of information about schedules and ticket prices that can be accessed quickly. By downloading the KAI Access application, the counter feels like it is in your hand, like the slogan buying tickets is as easy as updating status is one of PT. KAI's campaigns in the program buying tickets is easy.